Computer Simulations of Copper and Gold Nanowires and Single-wall Nanowires - Amorim, E. P. M; da Silva, A. J. R; da Silva, E. Z (Journal of physical chemistry. C, 2008)
Copper and gold nanowires under tension evolve to form linear atomic chains (LACs), and the study and understanding of this evolution is an important subject for the development of nanocontacts. Here we study the differences and similarities between copper and gold nanowires (NWs) under stress along the [111] crystallographic direction until their rupture using tight-binding molecular dynamics. In both metals, the first significant rearrangement occurs due to one inside atom that goes to the NW surface. In an attempt to better understand this effect, for both metals we also consider hollow NWs where the inside atoms were excluded after the initial relaxation to create single-wall NWs (SWNWs). The dynamical evolution of these SWNWs provides insight on the formation of the constriction that evolves to form LACs. Studying the calculated forces supported by the NWs we show that SWNWs can sustain larger forces before the first major rearrangement in the copper and gold when compared to the original NWs.